A software framework for assessing the resilience of drinking water systems to disasters with an example earthquake case study. (September 2017) - Klise, Katherine A.; Bynum, Michael; Moriarty, Dylan; Murray, Regan
Abstract: Water utilities are vulnerable to a wide variety of human-caused and natural disasters. The Water Network Tool for Resilience (WNTR) is a new open source Python™ package designed to help water utilities investigate resilience of water distribution systems to hazards and evaluate resilience-enhancing actions. In this paper, the WNTR modeling framework is presented and a case study is described that uses WNTR to simulate the effects of an earthquake on a water distribution system. The case study illustrates that the severity of damage is not only a function of system integrity and earthquake magnitude, but also of the available resources and repair strategies used to return the system to normal operating conditions. While earthquakes are particularly concerning since buried water distribution pipelines are highly susceptible to damage, the software framework can be applied to other types of hazards, including power outages and contamination incidents. Highlights: Water Network Tool for Resilience (WNTR) is a new open source Python package. WNTR can model a wide range of disruptive incidents and repair strategies. An earthquake case study is used to demonstrate capabilities in WNTR. Resilience metrics include water service availability and population impacted.